Clinicopathological description of 43 oncocytic adrenocortical tumors: importance of Ki-67 in histoprognostic evaluation. (November 2018) - Renaudin, Karine; Smati, Sarra; Wargny, Matthieu; Al Ghuzlan, Abir; Aubert, Sébastien; Leteurtre, Emmanuelle; Patey, Martine; Sibony, Mathilde; Sturm, Nathalie; Tissier, Frédérique; Amar, Laurence; Bertherat, Jérôme; et al.
Abstract Oncocytic adrenocortical tumors are a rare subtype of adrenal tumors with challenging diagnosis and histoprognostic assessment. It is usually believed that oncocytic adrenocortical tumors have a more indolent clinical behavior than conventional adrenocortical tumors. As the Weiss score overestimates the malignancy of oncocytic adrenocortical tumors owing to intrinsic parameters, alternative scores have been proposed. The Lin–Weiss–Bisceglia score is currently recommended. We performed a large nationwide multicenter retrospective clinicopathologic study of oncocytic adrenocortical tumors. Among the 43 patients in our cohort, 40 patients were alive without disease, 2 patients died of their disease and 1 patient was alive with relapse after a median follow-up of 38 months (20–59). Our data revealed that over 50% of the oncocytic adrenocortical tumor cases were diagnosed as carcinoma whatever the classification systems used, including the Lin–Weiss–Bisceglia score. The exception is the Helsinki score, which incorporates the Ki-67 proliferation index and was the most specific prognostic score for oncocytic adrenocortical tumor malignancy without showing a loss in sensitivity. A comparison of malignant oncocytic adrenocortical tumors with conventional adrenocortical carcinomas matched for age, sex, ENS@T stage and surgical resection status showed significant better overall survival of malignant oncocytic adrenocortical tumors.